Preparation method of medium-temperature fast-curing latent curing agent of transition metal coordination heterocyclic

By coordinating and self-assembling transition metal ions with heterocyclic curing agents to form stable complexes, the problem of rapid curing and long storage period of latent curing agents for resins at medium and low temperatures is solved, realizing the efficient preparation and excellent performance of resin-based composite materials.

CN120040724BActive Publication Date: 2026-11-06BEIJING UNIV OF CHEM TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510175999.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2026-11-06
Estimated Expiration
2045-02-18

AI Technical Summary

Technical Problem

Existing latent curing agents for resins are difficult to cure rapidly at medium and low temperatures and have short storage periods at room temperature, which cannot meet the long process window requirements of resin systems for dry winding prepreg tapes. Furthermore, existing modification methods are complex, costly, and unsuitable for industrial production.

Method used

The transition metal ions and heterocyclic curing agents are coordinated and self-assembled to form stable complexes, which inhibit the catalytic activity of tertiary amines, extend the room temperature pot life, and deblock the ring-opening etherification reaction of the catalytic resin at 100-120℃ to achieve rapid curing.

Benefits of technology

The prepared transition metal coordination heterocyclic latent curing agent has a long shelf life at room temperature, rapid curing at medium and low temperatures, simple and efficient synthesis, and is suitable for industrial production, ensuring the temperature resistance and mechanical properties of resin-based composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120040724B_ABST
    Figure CN120040724B_ABST
Patent Text Reader

Abstract

The application provides a latent curing agent of transition metal coordination heterocyclic class and a preparation method thereof. The latent curing agent is self-assembled by forming a coordination bond between an empty orbital of a transition metal ion and a lone pair of electrons on a nitrogen atom on a heterocycle. Since the catalytic activity of the tertiary amine on the heterocycle is inhibited, the curing agent has a long storage period at room temperature. The coordination bond is broken at high temperature, and the released tertiary amine can continue to catalyze the ring-opening etherification polymerization of the oligomer monomer, so that the curing agent has the ability of medium-temperature and rapid curing. The preparation process provided by the application is simple, efficient, high-yield, and the raw materials are easy to obtain, and is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of resin curing agent technology, specifically to a method for preparing a latent curing agent of transition metal coordination heterocyclic type that cures rapidly at room temperature. Background Technology

[0002] Resin-based composite materials have been widely used in aerospace, automotive manufacturing, electronics, and construction due to their excellent mechanical properties, temperature resistance, and chemical resistance. Type IV hydrogen storage cylinders, as an important carrier for green and low-carbon transformation, are currently the mainstream equipment in the hydrogen storage field due to their high hydrogen storage density, high fatigue life, and high structural efficiency. Dry winding molding, which involves winding resin-impregnated fiber prepreg tapes onto the surface of a thermoplastic liner in a specific linear pattern, is a cutting-edge technology for the rapid manufacturing of Type IV hydrogen storage cylinders. However, existing dry winding prepreg tape resin systems have short room temperature storage periods, making it difficult to meet the long process window requirements of the winding process. Furthermore, commercially available latent curing agents, such as dicyandiamide and hydrazide compounds, typically require high curing temperatures >150°C, resulting in high energy consumption and slow molding speeds. Moreover, the low melting point of the Type IV hydrogen storage cylinder plastic liner makes it unable to withstand high curing temperatures. Therefore, designing and preparing a medium-to-room-temperature rapid-curing transition metal-coordinated heterocyclic latent curing agent remains a significant challenge.

[0003] Heterocyclic curing agents, as commonly used medium-temperature curing agents, typically cure at temperatures below 120℃. The cured resin-based composites exhibit good mechanical properties, electrical insulation, and heat resistance. However, due to their high curing activity, heterocyclic curing agents have a short room-temperature shelf life after mixing with resins, limiting their long-term storage capability as a single-component system. Research on the latent properties of heterocyclic curing agents is of great significance in meeting the requirements for achieving long room-temperature storage and long process windows in resin systems for dry-wound prepreg tapes. To date, numerous studies have focused on the latent modification of heterocyclic curing agents. For example, the patent "A Benzothiadiazole-Modified Imidazole Compound and Its Preparation Method and Application" employs a chemical modification method, introducing benzothiadiazole into the active site of the nitrogen atom at the 1-position of the imidazole ring. Through the electron-withdrawing and steric hindrance effects of benzothiadiazole, the room-temperature curing activity of the imidazole curing agent is passivated, thereby improving the shelf life of single-component epoxy resin systems. When the prepared benzothiadiazole-modified imidazole compound is used as an epoxy resin curing agent, the exothermic reaction temperature exceeds 140°C. While this method can extend the storage time at room temperature to some extent, the high curing temperature does not meet the heat resistance requirements of existing Type IV hydrogen storage cylinder plastic lining materials. Furthermore, the preparation process of this compound is complex, requiring the use of ionic catalysts and hazardous acid-binding agents such as sodium hydroxide and potassium hydroxide in a nitrogen atmosphere, and the high reaction temperature and long cycle make it unsuitable for large-scale industrial safe production. In addition, there are methods for preparing latent curing agents using microencapsulation technology, such as the patent "Preparation Method of Imidazole Microcapsules Based on Thio-Isocyanate Click Reaction and Oil-in-Oil Interfacial Polymerization". This method uses a mixture of imidazole and thiol monomers as the dispersed phase and a mixture of isocyanate and non-polar solvents as the continuous phase to form an oil-in-oil emulsion. Then, the imidazole core catalyzes the thiol-isocyanate click reaction at the interface of the two phases, resulting in microcapsules with polyurethane shells and imidazole cores, which can be used as latent curing agents for epoxy resins. However, the high polarity of imidazole substances makes microencapsulation very difficult, resulting in a complex preparation process, low imidazole encapsulation, and uncontrollable reactions. Furthermore, during epoxy resin curing, microcapsule wall material remains in the epoxy resin system, potentially negatively impacting the physical and mechanical properties of the cured epoxy resin. Overall, current latent curing agents for resins face the technical challenge of simultaneously achieving rapid curing at medium and low temperatures and long storage periods at room temperature, and are difficult to produce on a large scale, hindering industrial applications. To address the aforementioned issues, this invention designs and prepares a medium-to-room-temperature rapid-curing transition metal-coordinated heterocyclic latent curing agent. This latent curing agent utilizes the coordination self-assembly of transition metal ions and heterocyclic curing agents. The empty orbitals of the transition metal ions form coordination bonds with the lone pairs of electrons on the nitrogen atoms of the heterocycle, constructing a stable complex that effectively inhibits the catalytic activity of tertiary amines. This extends the room-temperature pot life of the resin system and broadens the process window of the prepreg tape.Under heating conditions of 100-120℃, the complex is desealed, releasing the tertiary amine to catalyze the ring-opening etherification polymerization reaction of the resin. This improves latency while ensuring rapid curing at room temperature, avoiding damage to the plastic liner caused by high curing temperatures and guaranteeing the overall performance of the gas cylinder. The synthesis process of this invention is simple, efficient, has a high yield, uses readily available raw materials, and is suitable for industrial production, opening up a broader application prospect for resin-based composite materials. Summary of the Invention

[0004] This invention provides a method for preparing a transition metal-coordinated heterocyclic latent curing agent that cures rapidly at room temperature. The agent is formed by the coordination self-assembly of transition metal ions and a heterocyclic curing agent. This heterocyclic latent curing agent constructs a stable complex by coordinating the empty orbitals of the metal ions with the lone pairs of electrons on the nitrogen atoms of the heterocycle, effectively inhibiting the catalytic activity of the tertiary amine. This results in a latent curing agent with a long shelf life at room temperature. Under heating conditions of 100-120°C, the complex decongests, and the released tertiary amine rapidly catalyzes the ring-opening etherification polymerization reaction of the resin, improving latency while ensuring rapid curing at room temperature. The transition metal-coordinated heterocyclic latent curing agent prepared by this invention extends the room temperature shelf life of the resin system, broadens the molding process window for winding and other processes, and features a simple, efficient, and controllable preparation process with low synthesis cost, making it suitable for large-scale production.

[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0006] A method for preparing a latent curing agent with a transition metal coordination heterocyclic structure that cures rapidly at room temperature, characterized by comprising the following preparation steps:

[0007] (1) Preparation of heterocyclic ligand precursor solution: Add heterocyclic curing agent and solvent to a three-necked flask with a condenser, heat and stir under nitrogen atmosphere to obtain a transparent and homogeneous heterocyclic ligand precursor solution.

[0008] (2) Preparation of hydrated transition metal salt solution: Under nitrogen atmosphere, hydrated transition metal salt is placed in a drying oven and dried at 60-80℃ for at least 4 hours. Then, hydrated transition metal salt and solvent are added to a three-necked flask with a condenser and stirred for 2-5 hours to obtain a homogeneous hydrated transition metal salt solution.

[0009] (3) Synthesis and preparation of latent curing agents with transition metal coordination heterocyclic structures:

[0010] The heterocyclic precursor solution prepared in step (1) was transferred into a three-necked round-bottom flask equipped with a mechanical stirrer and a reflux condenser. Then, the hydrated transition metal salt solution prepared in step (2) was slowly added to the three-necked flask. The mixture was stirred at 30-60°C for 3-5 hours under nitrogen atmosphere. After the reaction was completed, the experimental apparatus was removed, and the resulting mixture was naturally cooled to room temperature. Then, it was washed with excess deionized water, filtered, and dried to obtain a crude product. The crude product was dissolved in dichloromethane and then filtered. The dichloromethane solvent was removed from the filtrate by vacuum distillation. The product obtained by vacuum distillation was vacuum dried in a vacuum oven at 70°C for two days to finally obtain a crude product in the form of block powder. By further nano-sizing, a transition metal coordinated heterocyclic latent curing agent with a particle size between 50-200 nm was obtained.

[0011] (4) Compounding of curing agent system: Weigh an appropriate amount of the transition metal coordination heterocyclic latent curing agent prepared in step (3) and add it to the amine curing agent or acid anhydride curing agent. Stir for 5-10 min at 30-60℃ and 200-500 r / min. Then, use a pulse cycle of 50s (on) / 25s (off) for ultrasonic dispersion treatment for 20-60 min. The setting of this intermittent pulse cycle can effectively improve the dispersibility of the transition metal coordination heterocyclic latent curing agent in the amine curing agent or acid anhydride curing agent. On the other hand, the ultrasonic shutdown period can provide enough time for the heat in the system to dissipate, which helps to control the reaction temperature and slow down possible overheating reaction. In addition, the temperature during stirring and ultrasonic treatment should not exceed 80℃. Excessive stirring temperature will affect the complexation structure of the transition metal coordination heterocyclic thermal latent curing agent and reduce the latent effect. Finally, a compounded curing agent system for resin is obtained.

[0012] (5) Preparation of resin system: Weigh the curing agent system compounded in step (4) and add it to the resin matrix. Stir for 10-20 minutes at 25-80℃ and 200-500r / min until the curing agent and resin are fully mixed to obtain a resin / latent curing agent mixture system. Place it in an oven and cure it according to a step-by-step curing regime.

[0013] The molar ratio of the heterocyclic curing agent in step (1) to the hydrated transition metal salt in step (2) is 4-4.2:1-1.2.

[0014] The heterocyclic ligands mentioned in step (1) are one or more of the following: nitrogen-containing heterocyclic ligands, CN-containing ligands, carboxylic acid-containing ligands, N and O-containing polydentate ligands, and N / S-containing ligands; wherein the nitrogen-containing heterocyclic ligands are preferably one of 4,4'-bipyridine, 2,4'-bipyridine, 4-ethylpyrimidin-2-amine, 2-methylimidazolium, 2-ethylimidazolium, 2-phenylimidazolium, 2-ethyl-4-methylimidazolium, 4-phenylimidazolium, and 2-undecylimidazolium. One or more types; CN-containing ligands are preferably one or two of 2,4,6-tricyanophenyl and 2,4,6-tris(p-cyanophenylethynyl)benzene; carboxylic acid ligands are preferably one or more of phthalic acid, terephthalic acid, isophthalic acid, and mesitylene benzoic acid; N and O polydentate ligands are preferably one or two of 4,5-imidazolium dicarboxylic acid and biphenyl dicarboxylic acid; N / S ligands are preferably one or two of 2-mercaptopyridine and 4-mercaptopyridine.

[0015] The hydrated transition metal salt mentioned in step (2) is a hydrate of transition metal salts such as iron salt, cobalt salt, nickel salt, and copper salt. Preferably, it is one or more of the following: ferric chloride hexahydrate (FeCl3·6H2O), cobalt chloride hexahydrate (CoCl2·6H2O), nickel chloride hexahydrate (NiCl2·6H2O), and copper chloride dihydrate (CuCl2·2H2O). Correspondingly, in step (3), latent curing agents for transition iron ion coordinated heterocyclic epoxy resins, latent curing agents for transition cobalt ion coordinated heterocyclic epoxy resins, latent curing agents for transition nickel ion coordinated heterocyclic epoxy resins, and latent curing agents for transition copper ion coordinated heterocyclic epoxy resins can be prepared.

[0016] In steps (1) and (2), the solvents selected are good solvents for heterocyclic curing agents and hydrated transition metal salts. The solvents are mixed solvents of alcohols, esters or benzene organic solvents, including one or more of methanol, ethanol, n-butanol, ethyl acetate, butyl acetate, benzene, toluene and xylene; and the amount of the solvent used accounts for 50-90% of the total mass of the corresponding mixed solution system.

[0017] The transition metal coordination heterocyclic latent curing agent described in step (3) needs to undergo a two-stage nano-process. In the first stage, at least one of the following pulverizing equipment can be selected: vibration mill, high pressure roller mill, centrifugal mill, stirring mill, etc. In the second stage, at least one of the following pulverizing equipment can be selected: air jet mill, ball mill, etc. Both stages are carried out using an intermittent pulverizing process, with each pulverizing operation time ≤200s and temperature ≤60℃.

[0018] The resin-based curing agent system described in step (4) consists of 5-20 parts by weight of a transition metal coordination heterocyclic latent curing agent and 80-95 parts by weight of an amine curing agent or anhydride curing agent. The transition metal coordination heterocyclic epoxy resin latent curing agent can be selected from transition iron ion coordination heterocyclic epoxy resin latent curing agents, transition cobalt ion coordination heterocyclic epoxy resin latent curing agents, or transition nickel ion coordination heterocyclic epoxy resin latent curing agents. At least one of the following is a latent curing agent for epoxy resins with transition copper ion coordination heterocyclic structures; the amine curing agent is liquid at 25-60°C, preferably one or more of dimethylthiotoluenediamine, diethyltoluenediamine, triethylenetetramine, isophoronediamine, etc.; the anhydride curing agent is liquid at 25-60°C, preferably one or more of phthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, etc.

[0019] The resin matrix described in step (5) consists of a main resin and a diluent. The main resin can be selected from one or more of epoxy resin, vinyl resin, phenolic resin, bismaleimide resin, cyanate ester resin, polyimide resin, and polyurethane; wherein the epoxy resin is preferably a mixture of one or more of glycidyl ether, glycidyl ester, glycidyl amine, and hydantoin epoxy resin; the vinyl resin is preferably a mixture of one or more of bisphenol A acrylic vinyl ester resin, bisphenol A methacrylate vinyl ester resin, and phenolic epoxy vinyl ester resin; the phenolic resin is preferably a mixture of one or more of thermoplastic phenolic resin, thermosetting phenolic resin, and high-ortho-phenolic resin; the bismaleimide resin is preferably a mixture of one or more of bisphenol A diphenyl ether type bismaleimide resin, alkyl diphenylmethane type bismaleimide resin, and polymeric polyamine type bismaleimide resin. The mixture comprises one or more of the following: cyanate ester resin, preferably a mixture of one or more of bisphenol A type cyanate ester resin, bisphenol E type cyanate ester resin, and phenolic type cyanate ester resin; polyimide resin, preferably a mixture of one or more of monoether anhydride type polyimide, diether anhydride type polyimide, and ketone anhydride type polyimide; polyurethane, preferably a mixture of one or more of polyether type polyurethane, polyester type polyurethane, polyimide type polyurethane, and polyurea type polyurethane; diluent, preferably a mixture of one or more of butyl glycidyl ether, 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether, phenyl glycidyl ether, polypropylene glycol diglycidyl ether, alkyl glycidyl ether, glycerol glycidyl ether, benzyl glycidyl ether, 1,6-hexanediol diglycidyl ether, and neopentyl glycol diglycidyl ether; wherein the mass ratio of the main resin to the diluent is 100:10-30.

[0020] The resin / latent curing agent mixture prepared in step (5) was stored at room temperature, and the viscosity of the system was tested according to the "GB / T10247-2008 Viscosity Measurement Method". This test aims to explore the performance continuity of the resin system under storage conditions.

[0021] The heat curing process described in step (5) uses a forced-air oven for heating. The specific curing regime is as follows: a) first heat up to 60-90℃ and keep warm for 0.5-1h; b) then heat up to 100-120℃ and keep warm for 1-3h.

[0022] Invention Effects

[0023] Combining all the above technical solutions, the advantages and significant effects of this invention are as follows:

[0024] (1) The transition metal coordination heterocyclic latent curing agent prepared by the present invention is formed by coordination self-assembly of transition metal ions and heterocyclic curing agents. The heterocyclic latent curing agent is combined with the lone pair electrons on the nitrogen atom of the heterocycle through the empty orbital of the transition metal ion by coordination bond, forming a complex under certain conditions, which effectively inhibits the catalytic activity of tertiary amines. When used as a latent curing agent for resin, it has the advantages of long storage period at room temperature, high stability and good dispersibility.

[0025] (2) The transition metal coordination heterocyclic latent curing agent prepared in this invention is used as a curing agent for resin. Under heating conditions of 100-120℃, the coordination bonds in the latent curing agent break, releasing the heterocyclic curing agent to catalyze the resin to undergo ring-opening etherification polymerization reaction. It has high reactivity and can quickly cure the resin matrix under medium and ambient temperature conditions, ensuring that the resin-based composite material has excellent temperature resistance and mechanical properties.

[0026] (3) The synthesis process of the transition metal coordination heterocyclic latent curing agent prepared by the present invention is simple, efficient, has a high yield, and the raw materials are readily available, making it suitable for industrial production. Attached Figure Description

[0027] Figure 1 Isothermal DSC curves of epoxy resin / amine curing agent / imidazolium, modified imidazolium A, modified imidazolium B, and modified imidazolium C at 80℃ for 240 min;

[0028] Figure 2 Isothermal DSC curves of epoxy resin / amine curing agent / imidazole, modified imidazole A, modified imidazole B, and modified imidazole C at 120℃ for 60 min. Detailed Implementation

[0029] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but the present invention is not limited to these embodiments.

[0030] Example 1

[0031] (1) Synthesis and preparation of latent curing agent of transition metal coordinated imidazole epoxy resin: 110.16g of 2-ethyl-4-methylimidazolium was weighed into reaction flask A, 200ml of anhydrous methanol was added, and the mixture was stirred continuously for 10min at 30℃ and 200r / min to obtain a transparent and homogeneous imidazole precursor solution; then 42.62g of copper chloride dihydrate was weighed into jacketed reactor B, 200ml of anhydrous methanol was added, and the mixture was stirred continuously for 10min at 30℃ and 200r / min to obtain a hydrated copper salt solution. Cooling water was introduced into the jacket, and the prepared hydrated copper salt solution was added to reaction flask A in batches under stirring conditions of 30℃ and 300r / min. After the addition was completed, nitrogen protective gas was introduced and the reaction was continued for 2 hours. After the reaction was completed, the solvent in the product mixture was removed by vacuum evaporation and dried thoroughly to obtain a block solid product. The product was first coarsely crushed by stirring mill, and then ultrafinely processed by ball mill to obtain a powdered copper salt coordinated imidazole heat latent curing agent.

[0032] (2) Preparation of epoxy resin / latent curing agent system: 10 parts by mass of copper salt-coordinated imidazole thermal latent curing agent were added to 100 parts by mass of dimethylthiotoluene diamine curing agent solution. The mixture was stirred for 10 min at 50℃ and 300 r / min, followed by ultrasonic dispersion treatment with a pulse cycle of 50 s (on) / 25 s (off) for 35 min to obtain a compound curing agent system for epoxy resin. 27 parts by mass of the compound curing agent system were added to 100 parts by mass of bisphenol A glycidyl ether type epoxy resin E51. The mixture was stirred for 15 min at 50℃ and 300 r / min until the curing agent and epoxy resin were fully mixed to obtain the epoxy resin / latent curing agent system. The prepared resin system was stored at room temperature. The viscosity of the epoxy resin / latent curing agent system prepared in this embodiment was tested according to the "Viscosity Measurement Method" (GB / T10247-2008), and the results are recorded in Table 1. Test results: The resin system has a pot life of 30 days at room temperature, exhibiting a relatively long storage period at room temperature.

[0033] (3) Preparation and performance testing of resin castings: The uniformly mixed epoxy resin / latent curing agent system was placed in a vacuum drying oven and degassed for 15 minutes under a negative pressure of -100 kPa at 50°C. Then, a forced-air oven was used for curing. The specific curing regime was: a) heating to 90°C and holding for 1 hour; b) heating to 120°C and holding for 3 hours. After curing, the oven power was turned off, and the oven temperature was allowed to drop below 40°C before opening the oven door and removing the cured epoxy composite material. The temperature resistance of the resin castings was tested according to GB / T40396-2021, and the tensile and flexural properties were tested according to GB / T 2567-2008. The results are recorded in Table 1. Test results: The glass transition temperature of the resin system was 165°C, indicating good temperature resistance; the tensile strength of the resin castings was 82 MPa, and the flexural strength was 135 MPa, indicating good mechanical properties.

[0034] Test results show that the epoxy resin / latent curing agent system of this embodiment has a long room temperature service life, and the resin system has high temperature resistance. The resin casting obtained by rapid curing at medium and low temperatures exhibits excellent tensile strength and flexural strength.

[0035] Comparative Example 1

[0036] (1) Preparation of epoxy resin / curing agent system: Unmodified 2-ethyl-4-methylimidazole with the same imidazole content as in step 2 of Example 1 was added to 100 parts by weight of dimethylthiotoluene diamine curing agent solution. The mixture was stirred for 15 minutes at 50°C and 300 r / min to obtain a compound curing agent system for epoxy resin. 27 parts by weight of the curing agent system were added to 100 parts by weight of bisphenol A glycidyl ether type epoxy resin E51. The mixture was stirred for 15 minutes at 50°C and 300 r / min until the curing agent and epoxy resin were fully mixed to obtain the epoxy resin / curing agent system. The prepared resin system was stored at room temperature. The viscosity of the epoxy resin / curing agent system prepared in this example was tested according to GB / T10247 2008 Viscosity Measurement Method, and the results are recorded in Table 1. Test results: The resin system has a usable period of 3 days at room temperature, exhibiting a relatively short room temperature storage period.

[0037] (2) Preparation and performance testing of resin castings: The uniformly mixed epoxy resin / curing agent system was placed in a vacuum drying oven and degassed for 15 minutes under a negative pressure of -100 kPa at 50°C. Then, it was cured by heating in a forced-air oven. The specific curing regime was: a) heating to 90°C and holding for 1 hour; b) heating to 120°C and holding for 3 hours. After curing, the oven power was turned off, and the oven temperature was allowed to drop below 40°C before opening the oven door and removing the cured epoxy composite material. The temperature resistance of the resin castings was tested according to GB / T 40396-2021, and the tensile and flexural properties were tested according to GB / T 2567-2008. The results are recorded in Table 1. Test results: The glass transition temperature of the resin system was 160°C, indicating good temperature resistance; the tensile strength of the resin castings was 80 MPa, and the flexural strength was 130 MPa, indicating good mechanical properties.

[0038] Test results show that the use of unmodified 2-ethyl-4-methylimidazole in the epoxy resin / curing agent system in this comparison results in a shorter storage period at room temperature.

[0039] Example 2

[0040] (1) Synthesis and preparation of latent curing agent of transition metal coordinated imidazole epoxy resin: 110.16g of 2-ethyl-4-methylimidazolium was weighed into reaction flask A, and 200ml of anhydrous methanol was added. The mixture was stirred continuously for 15min at 30℃ and 300r / min to obtain a transparent and homogeneous imidazole precursor solution. Then, 59.48g of cobalt chloride hexahydrate was weighed into jacketed reactor B, and 200ml of anhydrous methanol was added. The mixture was stirred continuously for 15min at 30℃ and 150r / min to obtain a hydrated cobalt salt solution. Cooling water was introduced into the jacket, and the prepared hydrated cobalt salt solution was added to reaction flask A in batches under stirring conditions of 30℃ and 250r / min. After the addition was completed, nitrogen protective gas was introduced and the reaction was stirred for 2 hours. After the reaction was completed, the solvent in the resulting product mixture was removed by vacuum evaporation and dried thoroughly to obtain a block solid product. The product was first coarsely pulverized by stirring mill, and then ultrafinely processed by ball mill to obtain a powdered copper salt coordinated imidazole heat-latent curing agent.

[0041] (2) Preparation of epoxy resin / latent curing agent system: 10 parts by mass of cobalt salt coordinated imidazole thermal latent curing agent were added to 100 parts by mass of methyl nadic anhydride curing agent solution. The mixture was stirred for 10 min at 45℃ and 300 r / min, followed by ultrasonic dispersion treatment with a pulse cycle of 50 s (on) / 25 s (off) for 40 min to obtain a compound curing agent system for epoxy resin. 70 parts by mass of the compound curing agent system were added to 100 parts by mass of bisphenol A glycidyl ether type epoxy resin E51. The mixture was stirred for 20 min at 50℃ and 250 r / min until the curing agent and epoxy resin were fully mixed to obtain the epoxy resin / latent curing agent system. The prepared resin system was stored at room temperature. The viscosity of the epoxy resin / latent curing agent system prepared in this embodiment was tested according to the "Viscosity Measurement Method" (GB / T10247-2008), and the results are recorded in Table 1. Test results: The resin system has a pot life of 25 days at room temperature, exhibiting a relatively long storage period at room temperature.

[0042] (3) Preparation and performance testing of resin castings: The uniformly mixed epoxy resin / latent curing agent system was placed in a vacuum drying oven and degassed for 15 minutes under a negative pressure of -100 kPa at 50°C. Then, a forced-air oven was used for curing. The specific curing regime was: a) heating to 90°C and holding for 1 hour; b) heating to 120°C and holding for 3 hours. After curing, the oven power was turned off, and the oven temperature was allowed to drop below 40°C before opening the oven door and removing the cured epoxy composite material. The temperature resistance of the resin castings was tested according to GB / T40396-2021, and the tensile and flexural properties were tested according to GB / T 2567-2008. The results are recorded in Table 1. Test results: The glass transition temperature of the resin system was 168°C, indicating good temperature resistance; the tensile strength of the resin castings was 83 MPa, and the flexural strength was 132 MPa, indicating good mechanical properties.

[0043] Test results show that the epoxy resin / latent curing agent system of this embodiment has a long room temperature service life, and the resin system has high temperature resistance. The resin casting obtained by rapid curing at medium and low temperatures exhibits excellent tensile strength and flexural strength.

[0044] Comparative Example 2

[0045] In step (2), the stirring temperature of the cobalt salt-coordinated imidazole latent epoxy resin curing agent and the methyl nadic anhydride curing agent in the preparation of the epoxy resin / latent curing agent system was increased to 100°C and the stirring time was 30 min. The ultrasonic temperature for ultrasonic dispersion treatment with a pulse cycle of 50 s (on) / 25 s (off) was adjusted to 80°C and the ultrasonic time was adjusted to 60 min. Other aspects remained the same as in Example 2. The resin system prepared in this comparative example was stored at room temperature. The viscosity of the epoxy resin / latent curing agent system prepared in this example was tested according to the "Viscosity Measurement Method" in GB / T10247-2008, and the results were recorded in Table 1. Test results: The pot life of the resin system at room temperature is 11 days, which is a short storage period at room temperature. The temperature resistance of the resin casting was tested according to GB / T 40396-2021, and the tensile and flexural properties of the resin casting were tested according to GB / T 2567-2008. The results were recorded in Table 1. Test results: The glass transition temperature of the resin system is 158℃, which shows good temperature resistance; the tensile strength of the resin casting is 80MPa and the flexural strength is 131MPa, which shows good mechanical properties.

[0046] Test results show that excessively high stirring and ultrasonic temperatures can destroy the complex structure of transition metal-coordinated imidazole thermal latent curing agents, causing the complex to release the imidazole curing agent prematurely, catalyzing the epoxy resin to undergo ring-opening etherification polymerization and reducing the latent effect.

[0047] Example 3

[0048] (1) Synthesis and preparation of latent curing agent of transition metal coordinated imidazole epoxy resin: 110.16g of 2-ethyl-4-methylimidazolium was weighed into reaction flask A, and 200ml of anhydrous methanol was added. The mixture was stirred continuously for 15min at 40℃ and 200r / min to obtain a transparent and homogeneous imidazole precursor solution. Then, 42.62g of copper chloride dihydrate was weighed into jacketed reactor B, and 200ml of anhydrous methanol was added. The mixture was stirred continuously for 15min at 40℃ and 200r / min to obtain a hydrated copper salt solution. Cooling water was introduced into the jacket, and the prepared hydrated copper salt solution was added to reaction flask A in batches under stirring conditions of 40℃ and 350r / min. After the addition was completed, nitrogen protective gas was introduced and the reaction was stirred for 2.5h. After the reaction was completed, the obtained product mixture was evaporated under reduced pressure to remove the solvent and dried thoroughly to obtain a block solid product. The product was first coarsely crushed by stirring mill, and then ultrafinely processed by ball mill to obtain a powdered copper salt coordinated imidazole heat latent curing agent.

[0049] (2) Preparation of epoxy resin / latent curing agent system: 10 parts by mass of copper salt-coordinated imidazole thermal latent curing agent were added to 100 parts by mass of dimethylthiotoluene diamine curing agent solution. The mixture was stirred for 15 min at 45℃ and 300 r / min, followed by ultrasonic dispersion treatment with a pulse cycle of 50 s (on) / 25 s (off) for 40 min to obtain a compound curing agent system for epoxy resin. 27 parts by mass of the compound curing agent system were added to 100 parts by mass of bisphenol A glycidyl ether type epoxy resin E51. The mixture was stirred for 15 min at 50℃ and 300 r / min until the curing agent and epoxy resin were fully mixed to obtain the epoxy resin / latent curing agent system. The prepared resin system was stored at room temperature. The viscosity of the epoxy resin / latent curing agent system prepared in this embodiment was tested according to the "Viscosity Measurement Method" (GB / T10247-2008), and the results are recorded in Table 1. Test results: The resin system has a pot life of 29 days at room temperature, exhibiting a relatively long storage period at room temperature.

[0050] (3) Preparation and performance testing of resin castings: The uniformly mixed epoxy resin / latent curing agent system was placed in a vacuum drying oven and degassed for 20 minutes under a negative pressure of -100 kPa at 45°C. Then, a forced-air oven was used for curing. The specific curing regime was: a) heating to 90°C and holding for 1 hour; b) heating to 120°C and holding for 3 hours. After curing, the oven power was turned off, and the oven temperature was allowed to drop below 40°C before opening the oven door and removing the cured epoxy composite material. The temperature resistance of the resin castings was tested according to GB / T40396-2021, and the tensile and flexural properties were tested according to GB / T 2567-2008. The results are recorded in Table 1. Test results: The glass transition temperature of the resin system was 166°C, indicating good temperature resistance; the tensile strength of the resin castings was 83 MPa, and the flexural strength was 135 MPa, indicating good mechanical properties.

[0051] Test results show that the epoxy resin / latent curing agent system of this embodiment has a long room temperature service life, and the resin system has high temperature resistance. The resin casting obtained by rapid curing at medium and low temperatures exhibits excellent tensile strength and flexural strength.

[0052] Comparative Example 3

[0053] The process for preparing the epoxy resin / latent curing agent system in step (2) was modified as follows: 10 parts by mass of copper salt-coordinated imidazole thermal latent curing agent were added to 100 parts by mass of dimethylthiotoluene diamine curing agent solution, and stirred for 30 min at 45°C and 300 r / min. A compound curing agent system for epoxy resin was obtained. 27 parts by mass of the compound curing agent system were added to 100 parts by mass of bisphenol A glycidyl ether type epoxy resin E51, and stirred for 20 min at 50°C and 300 r / min until the curing agent and epoxy resin were fully mixed, thus obtaining the epoxy resin / latent curing agent system. The prepared resin system was stored at room temperature. Other aspects remained consistent with Example 3. The resin system prepared in this comparative example was stored at room temperature. The viscosity of the epoxy resin / latent curing agent system prepared in this example was tested according to GB / T10247-2008 Viscosity Measurement Method, and the results are recorded in Table 1. Test Results: The resin system has a usable life of 35 days at room temperature, exhibiting a relatively long storage period at room temperature. The temperature resistance of the resin casting was tested according to GB / T 40396-2021, and the tensile and flexural properties were tested according to GB / T 2567-2008. The results are recorded in Table 1. Test Results: The glass transition temperature of the resin system is 142℃, indicating relatively low temperature resistance; the tensile strength of the resin casting is 53 MPa, and the flexural strength is 82 MPa, indicating relatively low mechanical properties.

[0054] Test results show that in the compound curing agent system without ultrasonic treatment, there are still solid particles with large particle sizes. These particles exist as defect sources and affect the mechanical properties of the resin system.

[0055] In this example, the viscosity of the epoxy resin / latent curing agent system was tested according to GB / T10247-2008, "Viscosity Measurement Method," to investigate the performance persistence of the resin system under storage conditions. Ultimately, the number of days it takes for the resin system's viscosity to double was defined as the pot life of the resin system at room temperature. The temperature resistance of the resin casting was tested according to GB / T 40396-2021, and the tensile and flexural properties of the resin casting were tested according to GB / T 2567-2008. The data collected for this example are shown in Table 1.

[0056] Table 1 Performance evaluation results of each instance

[0057]

[0058] As shown in Table 1, the epoxy resin / latent curing agent systems prepared by adding transition metal coordinated imidazole epoxy resin latent curing agents in Examples 1 to 3 have a room temperature service life of up to one month, and the resin system has good temperature resistance. The obtained resin-based composite materials exhibit excellent tensile strength and flexural strength.

Claims

1. A method for preparing a resin system containing a latent, transition metal-coordinated heterocyclic curing agent that cures rapidly at medium to room temperature, characterized in that, The preparation steps include the following: (1) Preparation of heterocyclic ligand precursor solution: Add heterocyclic curing agent and solvent to a three-necked flask with a condenser, heat and stir under nitrogen atmosphere to obtain a transparent and homogeneous heterocyclic ligand precursor solution. (2) Preparation of hydrated transition metal salt solution: Under nitrogen atmosphere, hydrated transition metal salt is placed in a drying oven and dried at 60-80 °C for at least 4 h. Then, hydrated transition metal salt and solvent are added to a three-necked flask with a condenser and stirred for 2-5 h to obtain a homogeneous hydrated transition metal salt solution. (3) Synthesis and preparation of latent curing agents with transition metal coordination heterocyclic structures: The heterocyclic precursor solution prepared in step (1) was transferred into a three-necked round-bottom flask equipped with a mechanical stirrer and a reflux condenser. Then, the hydrated transition metal salt solution prepared in step (2) was slowly added to the three-necked flask. The mixture was stirred at 30-60 ℃ for 3-5 h under nitrogen atmosphere. After the reaction was completed, the experimental apparatus was removed, and the resulting mixture was naturally cooled to room temperature. Then, it was washed with excess deionized water, filtered, and dried to obtain a crude product. The crude product was dissolved in dichloromethane and then filtered. The dichloromethane solvent was removed from the filtrate by vacuum distillation. The product obtained by vacuum distillation was vacuum dried in a vacuum oven at 60-70 ℃ for two days to finally obtain a crude product in block powder form. Through further nano-sizing, the transition metal coordinated heterocyclic latent curing agent underwent a two-stage nano-sizing process. In the first stage, at least one of the following pulverizing equipment was selected: a vibration mill, a high-pressure roller mill, a centrifugal mill, and a stirred mill. In the second stage, at least one of the following pulverizing equipment was selected: an air jet mill and a ball mill. Both stages were carried out using an intermittent pulverization process, and the operation time for each pulverization was ≤200 minutes. At a temperature ≤ 60 ℃, a transition metal coordinated heterocyclic latent curing agent with a particle size between 50-200 nm was obtained. (4) Compounding of curing agent system: Weigh an appropriate amount of the transition metal coordination heterocyclic latent curing agent prepared in step (3) and add it to the amine curing agent or acid anhydride curing agent. The compounded curing agent system consists of 5-20 parts by mass of transition metal coordination heterocyclic latent curing agent and 80-95 parts by mass of amine curing agent or acid anhydride curing agent. The amine curing agent is liquid at 25-60 ℃ and the acid anhydride curing agent is liquid at 25-60 ℃. When compounding, stir for 5-10 min at 30-60 ℃ and 200-500 r / min. Then, use a pulse cycle of 50 s (on) / 25 s (off) for ultrasonic dispersion treatment for 20-60 min to obtain the compounded curing agent system. (5) Preparation of resin system: Weigh the curing agent system compounded in step (4) and add it to the resin matrix. Stir for 10-20 min at 25-80℃ and 200-500 r / min until the curing agent and resin are fully mixed to obtain a resin / latent curing agent mixture system. Place it in an oven and cure it according to the following step-curing regime: a) first heat up to 60-90℃ and keep it at 0.5-1 h; b) then heat up to 100-120℃ and keep it at 1-3 h. The molar ratio of the heterocyclic curing agent in step (1) to the hydrated transition metal salt in step (2) is 4-4.2:1-1.2; The heterocyclic ligand is one or more of 2-methylimidazole, 2-ethylimidazole, 2-phenylimidazole, 2-ethyl-4-methylimidazole, 4-phenylimidazole and 2-undecylimidazole; The hydrated transition metal salt is one or more of the hydrates of iron, cobalt, nickel, and copper salts.

2. The method for preparing a resin system containing a latent, room-temperature-curing, rapidly curing transition metal-coordinated heterocyclic curing agent according to claim 1, characterized in that, The hydrated transition metal salt is one or more of the following: ferric chloride hexahydrate (FeCl3·6H2O), cobalt chloride hexahydrate (CoCl2·6H2O), nickel chloride hexahydrate (NiCl2·6H2O), and copper chloride dihydrate (CuCl2·2H2O).

3. The method for preparing a resin system containing a latent, transition metal-coordinated heterocyclic curing agent that cures rapidly at medium to room temperature, as described in claim 1, is characterized in that... The solvents used in steps (1) and (2) are selected as good solvents for heterocyclic curing agents and hydrated transition metal salts. The solvents are mixed solvents of alcohols, esters or benzene organic solvents, including one or more of methanol, ethanol, n-butanol, ethyl acetate, butyl acetate, benzene, toluene and xylene; and the amount of the solvent used accounts for 50-90% of the total mass of the corresponding mixed solution system.

4. The method for preparing a resin system containing a latent, room-temperature-curing, rapidly curing transition metal-coordinated heterocyclic curing agent according to claim 1, characterized in that, The amine curing agent is one or more of dimethylthiotoluenediamine, diethyltoluenediamine, triethylenetetramine, and isophoronediamine; the anhydride curing agent is one or more of phthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, and methylnadic anhydride.

5. The method for preparing a resin system containing a latent, room-temperature-curing, rapidly curing transition metal-coordinated heterocyclic curing agent according to claim 1, characterized in that, The resin matrix is ​​composed of a main resin and a diluent. The main resin is selected from one or more of epoxy resin, vinyl resin, phenolic resin, bismaleimide resin, cyanate ester resin, polyimide resin and polyurethane, wherein the mass ratio of the main resin to the diluent is 100:10-30.

Citation Information

Patent Citations

  • Room-temperature long-storage-period photo-thermal dual-curing high-temperature-resistant resin system for fiber prepreg tape and preparation method thereof

    CN119144122A